Health Screening of Newly Resettled Refugees in a Primary Care Setting - LACOURSE, SYLVIA (R I Med J (2013), 2013)
Since October 2008, the Medicine/Pediatrics Primary Care Center (MPPCC) has been working with Rhode Island’s refugee resettlement agency to coordinate medial care for newly resettled adults and adolescent refugees. The process includes obtaining extensive screening labs and providing immunizations. This review discusses the results of selected screening tests for latent TB, stool parasites, vitamin D, and vaccine-preventable diseases, such as hepatitis, performed as part of the initial intake exam during the first two years of operation of the MPPCC Refugee Clinic.